The effects of placement method on multilingual learner success in higher education - Key Jr, William (TESOL Journal, 2024)
In the United States, many actors are pushing for the use of grade point average (GPA) as the main placement tool for gatekeeper math and English courses for community college students (Quarles, 2022; Scott-Clayton, 2018; Turk, 2017). One community college system (pseudonymously, SXCC) in a New England state has begun placing students in initial math and English classes based on self-reported GPA. There have been studies on the effects of placement changes of this type (Belfield & Crosta, 2012; Hodara & Cox, 2016; Ngo & Kwon, 2014; Scott-Clayton, 2012). However, studies have not included the effects of these changes on multilingual learners (MLLs).Using a census of every MLL placed in SXCC in the summer and fall of 2020 and the spring of 2021 (N = 12,603), a MANOVA found that MLL students in the SXCC system who were placed using previous placement methods had a higher overall GPA than students placed using self-reported GPA (M = 3.32, SD = 0.740; M = 2.01, SD = 1.27, respectively) and had higher satisfactory academic progress (SAP) (M = 102.98, SD = 51.52; M = 57.66, SD = 55.53, respectively), and took longer to enroll in English 101 (M = 5.11, SD = 3.55; M = 2.36, SD = 1.76, respectively).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tesj.835
Keywords: dept.edu; peer-reviewed